Fecal microbiota in patients with a stoma decreases anaerobic bacteria and alters taxonomic and functional diversities - Sakai, Shunsuke A.; Aoshima, Masato; Sawada, Kentaro; Horasawa, Satoshi; Yoshikawa, Ayumu; Fujisawa, Takao; Kadowaki, Shigenori; Denda, Tadamichi; Matsuhashi, Nobuhisa; Yasui, Hisateru; Goto, Masahiro; Yamazaki, Kentaro; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Colorectal cancer (CRC) is one of the most common malignant diseases. Generally, stoma construction is performed following surgery for the resection of the primary tumor in patients with CRC. The association of CRC with the gut microbiota has been widely reported, and the gut microbiota is known to play an important role in the carcinogenesis, progression, and treatment of CRC. In this study, we compared the microbiota of patients with CRC between with and without a stoma using fecal metagenomic sequencing data from SCRUM-Japan MONSTAR-SCREEN, a joint industry-academia cancer research project in Japan. We found that the composition of anaerobes was reduced in patients with a stoma. In particular, the abundance of Alistipes, Akkermansia, Intestinimonas, and methane-producing archaea decreased. We also compared gene function (e.g., KEGG Orthology and KEGG pathway) and found that gene function for methane and short-chain fatty acids (SCFAs) production was underrepresented in patients with a stoma. Furthermore, a stoma decreased Shannon diversity based on taxonomic composition but increased that of the KEGG pathway. These results suggest that the feces of patients with a stoma have a reduced abundance of favorable microbes for cancer immunotherapy. In conclusion, we showed that a stoma alters the taxonomic and functional profiles in feces and may be a confounding factor in fecal microbiota analysis.